Detection of a novel HLA‐A*11 variant, A*11:255, in a Taiwanese individual. (15th February 2017) - Yang, K. L.; Ng, J.; Lazaro, A.; Lin, P. Y.
Abstract : One nucleotide substitution at residue 532 of HLA‐A*11:02:01 results in a novel allele, HLA‐A*11:255 .